HUBUNGAN ANTARA FAKTOR KETURUNAN, JENIS KELAMIN DAN TINGKAT SOSIAL EKONOMI ORANG TUA DENGAN KEJADIAN OBESITAS PADA MAHASISWA DI UNIVERSITAS MALAHAYATI TAHUN 2020 - Muhammad Yusmansyah Lubis; Dessy Hermawan; Upik Febriani; Achmad Farich (HUMAN CARE JOURNAL, 2020)
Obesity is an increase in the total fat in our body, if found to be overweight, the figure is> 20% in men and 25% in women because of the high fat in the body. Obesity is greatly influenced by parents and environmental heredity.This study aimed to determine the relationship between heredity, sex and socioeconomic level of parents with obesity in students at Malahayati University in 2020. The type of research used is research with the Purposive Sampling method and case control approach. The sample in this study was the medical students of the University of Malahayati Bandar Lampung in 2017 consisting of 30 people who were not obese and 30 people who were obese. Data obtained through filling out questionnaires and microtoise scales. The data analysis technique to test the hypothesis is the chi square statistical test. There is a significant relationship between heredity and obesity by obtaining p-value = 0.002 with OR = 6.00, there is a significant relationship between sex and obesity by obtaining p-value = 0.002 with OR = 5.50 and there is a significant relationship between parents' socioeconomic level with the incidence of obesity with p-value = 0.004 with OR = 4.75. There is a significant relationship between heredity, sex and socioeconomic level of parents with the incidence of obesity in students at the university actually live in 2020